Disaster plan education: how we made and tested a video. Issue 1 (January 1996) - Gray, D
Abstract : OBJECTIVE: To describe the making and testing of a 40 minute video to educate staff about a hospitals disaster plan. METHODS: A disaster scene was created and 30 staff volunteers took part in the simulation of a major accident. The simulation was used to explain and demonstrate disaster triage. A multiple choice questionnaire was used to compare information recall in a group who had seen the video and a group who had read the written plan. RESULTS: Large numbers of hospital staff voluntarily watched the video. The video group scored significantly higher than the reading group (P < 0.01), with mean scores of 72% and 45% respectively. CONCLUSIONS: Videos have an impact lacking in written disaster plans and improve recall of emergency procedures.